A Novel ALDH2 Activator AD-9308 Improves Diastolic and Systolic Myocardial Functions in Streptozotocin-Induced Diabetic Mice - Hsiao-Lin Lee; Siow-Wey Hee; Chin-Feng Hsuan; Wenjin Yang; Jing-Yong Huang; Ya-Ling Lin; Chih-Neng Hsu; Juey-Jen Hwang; Shiau-Mei Chen; Zhi-Zhong Ding; Tung-Yuan Lee; Yu-Chiao Lin; et al. (MDPI AG, 2021)
Diabetes mellitus has reached epidemic proportion worldwide. One of the diabetic complications is cardiomyopathy, characterized by early left ventricular (LV) diastolic dysfunction, followed by development of systolic dysfunction and ventricular dilation at a late stage. The pathogenesis is multifactorial, and there is no effective treatment yet. In recent years, 4-hydroxy-2-nonenal (4-HNE), a toxic aldehyde generated from lipid peroxidation, is implicated in the pathogenesis of cardiovascular diseases. Its high bioreactivity toward proteins results in cellular damage. Mitochondrial aldehyde dehydrogenase 2 (ALDH2) is the major enzyme that detoxifies 4-HNE. The development of small-molecule ALDH2 activator provides an opportunity for treating diabetic cardiomyopathy. This study found that AD-9308, a water-soluble andhighly selective ALDH2 activator, can improve LV diastolic and systolic functions, and wall remodeling in streptozotocin-induced diabetic mice. AD-9308 treatment dose-dependently lowered serum 4-HNE levels and 4-HNE protein adducts in cardiac tissue from diabetic mice, accompanied with ameliorated myocardial fibrosis, inflammation, and apoptosis. Improvements of mitochondrial functions, sarco/endoplasmic reticulumcalcium handling and autophagy regulation were also observed in diabetic mice with AD-9308 treatment. In conclusion, ADLH2 activation effectively ameliorated diabetic cardiomyopathy, which may be mediated through detoxification of 4-HNE. Our findings highlighted the therapeutic potential of ALDH2 activation for treating diabetic cardiomyopathy.